Experimental study on heat transfer of the magnetorheological fluids - GENÇ, SEVAL (IOP PUBLISHING LTD, 2013)
Thermal conductivity of magnetorheological suspensions synthesized with iron powder and silicone oil is experimentally investigated for varying particle volume fractions (5, 20, and 40 vol%) of two different grades of iron (Fe) and magnetic field strengths. In order to determine the temperature range at which the thermal conductivity of MR fluids is more effective for different heat transfer applications, the experiments are done for three different temperature intervals in three different temperature ranges: from -20 to 0 degrees C, from 0 to 50 degrees C, and from 50 to 100 degrees C. In this study, ISO 8301 'Thermal insulation-determination of steady state thermal resistance and related properties-heat flow meter apparatus' is used. The thermal conductivity of the MR fluids shows an increase with increasing magnetic field and volume fraction in the temperature intervals from 0 to 50 degrees C and from 50 to 100 degrees C. In particular, there is a substantial enhancement in the thermal conductivity for the 50-100 degrees C temperature interval (enhancement ratio by almost 134% for 40SM at H = 150 G). However, the thermal conductivity shows a decrease in the lower temperature interval from 20 to 0 degrees C (a decrease by 42% for 40SM at 150 G), which could be due the effect of the thermal conductivity of silicone oil at lower temperatures. Although the heat transfer coefficient is higher for higher particle concentrations, the percentage increase is more pronounced for lower particle concentrations, especially in the 0 to 50 degrees C temperature interval (for the 40SM sample at 150 G 18% an enhancement for a 20 K temperature difference is observed, whereas for the 20% MR fluid sample, the enhancement is 34%).
Keywords: TRANSPORT